Peran ASEAN University Network dalam Regionalisasi Pendidikan Tinggi - Aziz, Wildan Abdul; Trihartono, Agus (University of Jember, 2021)
In 1995, ASEAN established the ASEAN University Network (AUN), a special body to handle higher education affairs in ASEAN. This study questions how the role of AUN in the process of higher education regionalization. This study uses the FOPA Model (Functional, Organizational, and Political Approaches) in analyzing the process of higher education regionalization in ASEAN through AUN. Data collection in this study uses two ways; literature study and interviews. The results of this study concluded that AUN in the process of higher education regionalization had a role as a facilitator and forum. In this case AUN seeks initiatives through two lines; system alignment and collaboration programs.